Autism Spectrum Disorders - Grabrucker, Andreas M (Exon Publications, 2021)
Autism spectrum disorders are developmental disorders. Individuals with autism spectrum disorders develop differently. These differences are usually present in social interaction, communication, and sensory processing, and become visible through a wide variety of behavioral responses that differ from individuals without autism spectrum disorders. Despite significant research efforts, the exact causes of autism spectrum disorders remain poorly understood; however, researchers have gained extensive insights into possible pathomechanisms, even at the molecular level of cells. Many diagnostic criteria have been developed, adapted, and improved. The eight chapters in this book highlight the current state-of-the-art in many areas of autism spectrum disorders. Chapter 1 provides an overview of the epidemiology of autism spectrum disorders and the current knowledge of the underlying pathogenic mechanisms. Chapter 2 summarizes the diagnostic criteria and procedures and highlights present and upcoming therapeutic strategies. Chapter 3 reviews the adverse events and trauma in people with autism spectrum disorders. Chapters 4 and 5 focus on atypical sensory processing, and Chapter 6 discusses the genetic overlap of autism spectrum disorders with other neuropsychiatric disorders such as attention deficit hyperactivity disorder (ADHD), depression, and schizophrenia. Chapter 7 focuses on the contribution of abnormalities in mitochondria, and chapter 8 discusses gut-brain interactions and a potential role for microbiota in autism spectrum disorders. This book is aimed primarily at clinicians and scientists, but many areas will also be of interest to the layperson.